Potentials of omega-3 fatty acids as therapeutic drugs and its obstacles in the pathway: A critical review - Saiqa Afroze; Ashok Kumar Janakiraman; Baskaran Gunasekaran; Sinouvassane Djearamane; Ling Shing Wong (GarVal Editorial Ltda., 2024)
Context: Eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid are the significant members of the ω-3 fatty acid group. Their beneficial pharmacological effects open new paths for therapeutics. Aims: To provide an updated overview of the source, chemical features, pharmacological effects, dosage forms, and patents of omega-3 fatty acids and analyze the limitations in visualizing them as an active drug for treatment. Methods: PubMed, Science Direct, Google Scholar, Springer Link, Google Patent, and Espacenet were used for the systematic search for articles from 2011-2023. Specific keywords were used for the search. For the screening process, articles related to the topic with full text in English were chosen. Two independent researchers analyzed, extracted, and summarized relevant data in Excel for data presentation. Results: 196 references were chosen for this review. In summary, lipid mediators from omega-3 fatty acids were found to exert anti-inflammatory functions, modulate signal transactions, regulate gene expression, and work as anti-microbial agents. These functions positively impact the cardiovascular, immune, metabolic, nerve, and optic systems. Despite abundant benefits, most products related to n-3 fatty acids were concentrated on utilizing as adjuvants and supplements. The source-related issues, complex extraction methods, oxidative instability, cost, side effects of formulations, complicated patent processes, and lenient regulation for supplements have been viewed as the reasons. Conclusions: Omega-3 fatty acids are a safe choice as a therapeutic drug for elderly patients, pregnant women, and children with disorders. Microbial production, low-energy formulation, and the use of natural emulsifiers can resolve the obstacles in this pathway.